Development and Application of an MRT-qPCR Assay for Detecting Coinfection of Six Vertically Transmitted or Immunosuppressive Avian Viruses - Li, Xiao; Zhang, Keran; Pei, Yu; Xue, Jia; Ruan, Sifan; Zhang, Guozhong (Frontiers in Microbiology, 2020)
Marek’s disease virus (MDV), reticuloendotheliosis virus (REV), avian reovirus (ARV), chicken infectious anemia virus (CIAV), infectious bursal disease virus (IBDV) and fowl adenovirus (FAdV) are important cause of disease in poultry. To investigate the infection status of the above six viruses in chickens in China, 1,187 samples from chicken flocks were collected and tested using a newly developed multiplex reverse transcription quantitative real-time PCR (MRT-qPCR) assay in the study. A series of validation tests confirmed that the MRT-qPCR assay has high specificity, sensitivity and repeatability. As for six detected pathogens, CIAV had the highest detection ratio, while ARV was not detected in any samples. In the spleen samples, the co-infection rate for MDV and CIAV was 1.6%, and that for REV and CIAV was 0.4%. In the bursa samples, the co-infection rate for FAdV and CIAV was 0.3%, and that for IBDV and CIAV was 1%. In the thymus samples, the co-infection rates for MDV and CIAV and for REV and CIAV were both 0.8%. Our study indicates that the co-infection of these viruses was existing in chickens in China. Through the detection of clinical samples, this study provides data on the co-infections of the above six pathogens and provides a basis for the further study of viral co-infection in chickens.